Development and testing of fast curing, mineral-impregnated carbon fiber (MCF) reinforcements based on metakaolin-made geopolymers. (February 2021) - Zhao, Jitong; Liebscher, Marco; Michel, Albert; Junger, Dominik; Trindade, Ana Carolina Constâncio; de Andrade Silva, Flávio; Mechtcherine, Viktor
Abstract: Mineral-impregnated, carbon ﬁber composites (MCF) are a promising alternative to conventional concrete reinforcements. For the efficient industrial production of MCF, sufficient processing time for the impregnation suspension must be ensured. In the present investigation, a metakaolin-made geopolymer (GP) has been developed and tested for this purpose. The impregnation of carbon-fiber yarns was performed continuously and automated. Subsequently, the MCF were heat-treated at 75 °C to accelerate the reaction processes. The mechanical performance of MCF gradually increased in the advancement of the curing process from 2 to 8 h, which is attributed to the greater extent of geopolymerization. In such extended curing, thermogravimetric and microscopic analysis showed indeed a more "reacted" microstructure but also a higher content of voids. After heating for 8 h, the tensile strength and Young's modulus of MCF reached 2960 MPa and 259 GPa, respectively, when related to the yarn cross-sectional area.